Picture Series Revealed Students’ Ability In Writing Narrative Text To The Junior High School Students - Idla Fitri Linggarni (Proceedings of The ICECRS, 2021)
The objective of this research were to improve students’ writing skill with implementation on 9th grade of SMP Negeri 2 Buduran in the academic year 2019/2020. The research aim to find whether there was any significant effect in learning achievement of writing skill between an ordinary teaching learning with taught by using picture series. The background of this research has been conducted on 9th grade of SMP Negeri 2 Buduran with high significance of students’ score before and after using picture series media. The researcher choose a quantitative method in this research and the result of the test was analyzed using t-test formula and the result was high level it means accurate for the instrument. The students’ mean pre-test and post-test score were showed that there was difference of the score which is increase the students’ writing skill using picture series. The students’ mean pre-test score is (67.66) and the mean post-test score is (81.34).